2023
DOI: 10.1039/d3qo00879g
|View full text |Cite
|
Sign up to set email alerts
|

SO2ClF-promoted chlorination-oxidation of 2-methylindoles: a one-step synthetic method to access 2,3-difunctionalized indoles

Abstract: A direct and one-step method for the synthesis of 3-chloro-2-formylindoles with SO2ClF is reported. This tandem system consists of double electrophilic chlorination and deprotonation, nucleophilic addition of H2O to the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This result is consistent with our recent work on SO 2 ClF-promoted chlorination-oxidation of 2-methylindoles. [20] It is important to note that no overchlorination on the aromatic ring was observed for all cases under the current optimal conditions. Unfortunately, the present system has some limitations.…”
Section: Resultsmentioning
confidence: 78%
“…This result is consistent with our recent work on SO 2 ClF-promoted chlorination-oxidation of 2-methylindoles. [20] It is important to note that no overchlorination on the aromatic ring was observed for all cases under the current optimal conditions. Unfortunately, the present system has some limitations.…”
Section: Resultsmentioning
confidence: 78%
“…For example, para -methoxybenzylidenecyclobutanol 3a afforded chlorinated product 4a with a Z -olefin moiety in only 10 min under otherwise identical conditions, as shown in Scheme . Sulfuryl chlorofluoride functioned as an electrophilic chlorination reagent and reacted with electron-rich alkene in compound 3a through a similar pathway as the known ring-opening fluorination process . Switching the solvent from Et 2 O to THF resulted in an increase of the yield, giving product 4a in 67% yield (Scheme B).…”
mentioning
confidence: 96%
“…Recently, we have shown that strong electrophilic sulfuryl chlorofluoride (FSO 2 Cl) displays significantly different reactivity from alkyl or aryl sulfonyl chlorides . It can readily form EDA complexes with weak electron donors, propargyl alcohols, to trigger the FSO 2 radical formation .…”
mentioning
confidence: 99%